2016
DOI: 10.1016/j.micres.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of Bacillus subtilis subsp. subtilis and B. amyloliquefaciens against Macrophomina phaseolina: SEM study of fungal changes and UV-MALDI-TOF MS analysis of their bioactive compounds

Abstract: The antifungal effect of Bacillus subtilis subsp. subtilis PGPMori7 and Bacillus amyloliquefaciens PGPBacCA1 was evaluated against Macrophomina phaseolina (Tassi) Goid. Cell suspension (CS), cell-free supernatant (CFS) and the lipopeptide fraction (LF) of PGPMori7 and PGPBacCA1 were screened against three different M. phaseolina strains. CS exhibited the highest inhibitory effect (around 50%) when compared to those of CFS and LF, regardless of the fungal strain studied. The synthesis of lipopeptides was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 36 publications
4
58
0
8
Order By: Relevance
“…There are also many researches that show good results for bean diseases such as Macrophomina phaseolina (Torres et al, 2016), X. axonopodis pv. phaseoli (Zanatta et al, 2007;Sallan, 2011), Pseudomonas savastanoi pv.…”
Section: Introductionmentioning
confidence: 99%
“…There are also many researches that show good results for bean diseases such as Macrophomina phaseolina (Torres et al, 2016), X. axonopodis pv. phaseoli (Zanatta et al, 2007;Sallan, 2011), Pseudomonas savastanoi pv.…”
Section: Introductionmentioning
confidence: 99%
“…Torres et al (2016) reportaron una inhibición del 56.5±2.1% sobre el crecimiento micelial de Macrophomina phaseolina mediante la técnica de cultivo dual, utilizando suspensión celular de B. amyloliquefaciens. De acuerdo con lo observado en el trabajo de Torres et al (2016) y en el presente trabajo, se demuestra que la capacidad biocontroladora de B. amyloliquefaciens se ve afectada por la naturaleza del patógeno, ya que al confrontar la suspensión celular de B. amyloliquefaciens con zoosporas de P. capsici en medio de cultivo líquido, se observa una inhibición germinativa del 88.15%.…”
Section: Discussionunclassified
“…Por otro lado, Chen et al (2016b), reportaron una tasa de germinación de zoosporas de P. capsici del 100% al ser confrontadas con filtrados obtenidos de un cultivo de Streptomyces plicatus, donde los ingredientes del medio de cultivo fueron papa y sucrosa; sin embargo, los resultados que obtuvieron al utilizar filtrados provenientes de medios de cultivo and B. thuringiensis, respectively. Torres et al (2016) reported 56.5±2.1% inhibition of Macrophomina phaseolina mycelial growth using the dual crop technique and cell suspension of B. amyloliquefaciens. According to Torres et al (2016) and to the present study, it has been proven that B. amyloliquefaciens biocontrol capacity is affected by the pathogen's nature, because when the cell suspension of B. amyloliquefaciens was mixed with P. capsici zoospores in a liquid culture medium, it caused 88.15% germination inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations